SISTEM INFORMASI PENJUALAN FARMASI SAUDARA MENGGUNAKAN ANDROID - Firdalius, Fitri; Djesmedi, Dinda; Agung, Maharian; Marfalino, Hari (JENTIK, 2024)
To meet the needs of Saudara Pharmacy, there will be an Android-based sales information system that uses the Waterfall method to manage the sales of medicines and other health products. Need analysis, system design, implementation, testing, and maintenance are the stages of the Waterfall method, chosen because of its systematic and sequential approach. This method makes it easy for the developer team to ensure that each stage of development is well completed before proceeding to the next stage. Information is collected about the operational needs of Saudara Pharmacy at the stage of needs analysis. This data is used to create a system that can monitor the stock of drugs, automate the sales process, and provide direct sales reports. The easy-to-use Android application to implement allows pharmacy employees to perform sales transactions quickly and accurately. Drug barcode scanning, inventory management, sales transaction recording, and the creation of daily sales reports are the main features of this app. The system is tested to ensure that the application works properly and has no errors. In addition, user feedback is collected and studied to enable improvements and features. It is expected that the Android-based Sales Information System at Saudara Pharmacy will improve operational efficiency, reduce sales recording errors, and provide accurate data for management to make decisions. Moreover, the system will increase customer satisfaction by providing faster and more accurate services.